Upaya Pembentukan Karakter Melalui Kelompok Belajar Alat Musik Angklung pada Siswa Kelas 5 SDN 068083 Medan - Apriliani, Eryasti; Sinaga, Randa Putra Kasea (Yayasan Literasi Sains Indonesia, 2023)
Character education is a very important educational process aimed at every child of the nation. The education is focused on instilling and developing values, attitudes, quality behavior, noble character, and noble ethics for the nation's children. In forming character, it is important to be instilled and formed from an early age, which means that at elementary school age this educational process must be maximized. This character-building effort through angklung musical instrument learning groups for grade 5 students of SDN 0680083 Tj.Rejo is an activity formed by the USU partner campus program Batch 2 which aims to instill the values of the nation's character designed in the archipelago module on 16 topics discussed. On the basis of these activities, the author also sees opportunities that exist from school facilities, namely angklung musical instruments that must be utilized, namely angklung musical instruments that are still lacking teaching at the school. The angklung musical instrument learning group is expected to have an effective impact because the angklung musical instrument game must be played in groups with good harmonization from each member, from that the attitude of discipline, tolerance, care, deliberation and national character values will be formed in each child who is a member of the study group. The method in this study is a qualitative descriptive method that seeks to describe the process, effort and impact of learning angklung musical instruments through study groups to shape the character of grade 5 students of SDN 068083 Tj.Rejo.